The Effect of Silicon on Chlorophyll and Abscisis Acid Contect on Several Cultivar of Soybean Under Drought Stress - Yonny Koentjoro; Djoko Purnomo; Edi Purwanto; Sukendah (Future Science)
Silicon is the second most abundant in the soil and Silicon could be considered as an essential element in many crops to enhancing growth and alleviating biotic and abiotic stresses. Silicon present exclusively in the form of silicic acid (H4SiO4). It is absorbed by plants in the form of silicic acid. The aim of research is knowing the content of Chlorophyll and Abscisic Acid of soybean under drought stress by silicon application. The different levels of Silicon were tested in a pot experiment to assess their effects on chlorophyll content and Abscisic acyd on several cultivar of soybeans under drought stress. The results show that there is no interaction between each treatment cultivar and silicon. The absorbance value of chlorophyll leaf using spectrophotometer shows that chlorophyll content differs significantly on each cultivar of soybeans. The increasing application of silicon concentration tends to increase chlorophyll content but decreases the levels of Abscisic Acid (ABA) in leaves.